Aggregation with price variation and heterogeneity across consumers - Bente Halvorsen; Bodil M. Larsen (Statistics Norway, Research Department, 2006)
In the aggregation literature, prices and price and income derivatives are often assumed not to vary across consumers. These assumptions may not be fulfilled: prices often vary and consumers are heterogeneous in the way they respond to price and income changes. In this paper we develop and illustrate a framework for consistent aggregation over consumers within an Almost Ideal Demand System (AIDS) model where prices, total expenditure and the response to these variables vary across consumers. We show how the frameworks previously discussed in the literature on aggregation of an AIDS model may be written as a special case within this general framework. The method may easily be adapted to any functional form.
Keywords: D1; 330; Aggregation; Consumer demand; Heterogeneity